1982
DOI: 10.1136/bmj.285.6342.617
|View full text |Cite
|
Sign up to set email alerts
|

Attendance at a breast screening clinic: a problem of administration or attitudes.

Abstract: In a study of why a sample of women, aged 45-64 and registered with a group practice in Edinburgh, attended or did not attend the Edinburgh Breast Screening Clinic demographic, aetiological, social, and perceptual characteristics of attendees and non-attenders were compared. Similar proportions of attendees and non-attenders knew the chance of a breast lump being cancer and were aware of the benefits of early diagnosis and treatment. The study, however, suggests that non-attenders saw the screening clinic as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
4

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(24 citation statements)
references
References 10 publications
2
18
0
4
Order By: Relevance
“…There is evidence that those who seek consultation quickly have lives that are less busy and stress-filled (Burgess et al, 2000). The breast cancer screening literature also finds that difficulties related to family or work are a common reason that women give for not attending breast screening (French et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that those who seek consultation quickly have lives that are less busy and stress-filled (Burgess et al, 2000). The breast cancer screening literature also finds that difficulties related to family or work are a common reason that women give for not attending breast screening (French et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of breast screening non-attenders have been reported to exaggerate difficulties such as home and work commitments." 45 …”
Section: Effort Attending Assessment (Factor 4)mentioning
confidence: 99%
“…Ten of the papers showed a significant positive association between the two screening behaviours, such that those who have participated in breast screening are more likely also to attend for cervical screening, 87,118,144,[158][159][160][161][162][163][164] and the remaining two showed no association.…”
Section: Cervical Screening Practicesmentioning
confidence: 99%
“…Ten out of 12 papers found positive associations between mammography use and health prevention behaviours but, again, none of these studies had baseline measures so the direction of the association cannot be ascertained. 87,118,133,146,[158][159][160][161]164,172 Two studies reported no association. 123,136 One study found positive associations between mammography and tetanus immunisation, sigmoidoscopy screening and faecal occult blood testing, but no associations between breast screening and smoking behaviours, exercise, seatbelt use, aspirin or hormone replacement therapy (HRT) use.…”
Section: Other Preventive Health Behavioursmentioning
confidence: 99%